Biosynthetic timing and substrate specificity for the thiopeptide thiomuracin - Zhang, Zhengan (J Am Chem Soc, 2016)
The biosynthesis of the thiopeptide thiomuracin is a well-orchestrated process involving a multitude of posttranslational modifications. We show that six Cys residues of a precursor peptide are first cyclodehydrated and oxidized to thiazoles in an ordered, but non-linear fashion that is leader peptide-dependent. Then four alcohols are glutamylated and converted to alkenes in a C-to-N terminal directional process that is leader peptide-independent. Finally, two of these alkenes undergo a formal [4+2] cycloaddition to form a tri-thiazole-substituted pyridine macrocycle. We describe here the factors that govern the substrate specificity and order of biosynthetic events that turn a ribosomal peptide into a powerful antibiotic.